Relation of Vitamins in Diabetes Melliatus - Lotake, Dr. Vaibhav D.; Barsode, Dr. Supriya (International Journal of Innovative Research in Medical Science, 2018)
Introduction Diabetes is a chronic metabolic disorder which is linked to energy metabolism, particularly carbohydrate and fat. Obesity and physical inactivity are shown to be the major risk factors for type 2 diabetes (T2DM). Oxidative stress may also contribute to increase in blood glucose levels, thus contribute to the pathogenesis of T2DM by increasing insulin resistance or impairing insulin secretion.[1] The consequences and complications of diabetes are due to imbalance between free radical formation and their control by natural antioxidants.[2] Thus nutrients having antioxidant function are important in disease development and control also non oxidant vitamins have also shown relationship with diabetes.[3] Long-term treatment of diabetic patients with metformin may cause a higher risk of developing vitamin B-12 deficiency.[4] Vitamin A plays important role as antioxidant, thus helping to maintain the organism’s homeostasis when subjected to various forms of stress.[5] Vitamin B6 consists of a group of three compounds: Pyridoxal, pyridoxine and pyridoxamine, and their corresponding phosphorylase forms and the active form of this vitamin is pyridoxal-5’-phospate (PLP). In new diabetic patients lower PLP concentrations were found as compared to non-diabetic persons.[6] Niacin or B3, Nicotinic acid is a component of NAD and NADH, which are essential for ATP production and energy efficiency at the cellular level and has been found to increase HDL-cholesterol, decreases TG and LDL cholesterol.[7] As T2DM is an oxidative stress disease; vitamin B12 and folic acid deficiencies in diabetic subjects have been found associated to oxidative stress so it is conceivable that vitamin B12 deficiency should be considered a risk factor for diabetic complications.[8] Plasma vitamin C concentrations have been inversely correlated to glycosylated hemoglobin and fasting and postprandial blood, Vitamin C has also been shown to reduce anxiety levels.[9] and supplementation for 3 months of vitamins C and E decreases hypertension, blood glucose while increasing superoxide dismutase and glutathione levels.[10] Vitamin D may play an important role in modifying the risk of diabetes.[11] The role of vitamin D in the function of pancreatic cells can be mediated by the union of 1,25-dihydroxyvitamin D to its receptors in the beta cell.[12]